Profesionalisme Guru TK: Ditinjau dari Aspek Gaji dan Motivasi Kerja di Kecamatan Tawang dan Cipedes - Abdullah Napi Alas’ari, Aji; Hendri Mulyana, Edi; Qonita, Qonita (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study addresses the scarcity of research on the professionalism of kindergarten teachers in relation to salary and work motivation, despite its substantial impact on the quality of early childhood education in Indonesia. Using a qualitative case study approach, the research involved six kindergarten teachers (n = 6) from Tawang and Cipedes sub-districts, selected through purposive sampling. Data were collected through semi-structured interviews, direct observation, and document analysis, and analyzed thematically to identify recurring patterns and themes. Findings reveal that low salary remains a major barrier to improving teacher welfare and professionalism, whereas intrinsic work motivation—such as passion for teaching and commitment to children’s development—remains consistently high among participants. School-led initiatives, including professional training and non-financial rewards, positively influence teacher confidence and professional competence, yet do not fully address financial challenges. The study confirms the relevance of Herzberg’s two-factor theory, indicating that both salary (hygiene factor) and motivation (motivator factor) are critical for fostering professionalism in early childhood education. Ethical approval was obtained from relevant authorities, and informed consent was secured from all participants. The results offer theoretical insights into teacher professionalism and practical implications for policymakers and school leaders to design effective welfare policies and professional development programs